O3A.5 Environmental dust exposure from gold mine waste dumps and respiratory health effects in johannesburg, south africa. (April 2019) - Iyaloo, Samantha; Kootbodien, Tahira; Naicker, Nisha; Mathee, Angela; Kgalamono, Spo; Wilson, Kerry; Rees, David
Abstract : Background: Thousands of people living in close proximity to gold mine waste dumps (GMWDs), are exposed to wind-swept, silica-rich dust. The effects on respiratory heath consequent on this exposure are largely unknown. Objective: To examine associations between environmental GMWD dust exposure and respiratory health effects in adults. Methods: This was a cross-sectional study of 93, 133 and 84 people in high (home <500 m from GMWD), moderate (500 m-1km) and low (>20 km) exposure groups respectively. We calculated a cumulative exposure index (CEI) based on exposure groups and years of residence. Participants were interviewed for respiratory symptoms, had chest X-rays (read by three experienced readers for tuberculosis and silicosis) and spirometry. We used multivariate logistic regression to examine the effect of dust exposure on respiratory health, and multiple linear regression to determine if CEI was associated with% predicted FEV1 and FVC. We adjusted for socioeconomic status, smoking and occupational and biomass fuel exposure. Results: Being in the high exposure group versus the low was associated with elevated adjusted odds ratios (aORs) for upper respiratory (aOR: 2.76, 95% CI: 1.28–5.97) and ocular symptoms (aOR: 4.68; 95% CI: 1.87–11.68), chest wheezing (aOR: 3.78; 95% CI: 1.60–8.96) and spirometry-diagnosed COPD (aOR: 8.17; 95% CI: 1.01–65.85). We found similar associations for the high versus medium exposure groups, but no significant associations in the medium relative to the low group. Exposure had no significant effect on the risks of chronic bronchitis and tuberculosis. We found similar significant results for CEI as for the exposure groups analyses. On linear regression, CEI was not associated with% predicted FEV1, but, surprisingly, FVC was positively associated with CEI. No participant had radiological features of silicosis. Conclusion: Residents residing <500 m from GMWDs had elevated aORs for respiratory health effects. Both exposure measures (exposure groups and CEI) yielded similar results.